REVIEW : HUBUNGAN MENGKONSUMSI KOPI DENGAN TEKANAN DARAH TINGGI - Fajar Surya Alam; Muhammad Ikhsan Prawira Negara (Universitas Islam Al-Ihya Kuningan, 2024)
Coffee is popular among various groups of teenagers, young adults and older people, both men and women. Apart from that, coffee is said to be a risk factor for hypertension. Because coffee contains caffeine. Caffeine has the property of increasing blood pressure. This study aims to determine the relationship between coffee and hypertension. This research uses a Literature Review design by collecting several journals via Google Scholar, and SINTA. In this study, people who have a habit of consuming moderate levels of coffee (600-800 ml) have a significant value (p value) of 0.010, where this value is smaller than the α value (0.05), so it can be concluded that there is a relationship between the frequency of coffee consumption and blood pressure in hypertensive patients in the working area of ​​the Dau Public Health Center, Malang Regency. If you look at the correlation coefficient (r), it is in the coefficient range of 0.40-0.599, namely 0.424, then the relationship between these variables is quite strong. There is a relationship between consuming coffee and blood pressure. It's just that the increasing frequency of coffee consumption will increase the increase in blood pressure.